Alan Hollinghurst : writing under the influence - Mendelssohn, Michèle; Flannery, Denis, 1962- (Manchester University Press, 2016)
An edited collection on Alan Hollinghurst, one of Britain's leading contemporary novelists with an outstanding international reputation.